2020
DOI: 10.1016/j.chest.2019.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Pharmacotherapy for Common Sleep Disorders in Pregnancy and Lactation

Abstract: Sleep disturbances are common in pregnancy, and sleep disorders may worsen or present de novo in the course of gestation. Managing a pregnant patient is complicated by the risk of teratogenicity, pharmacokinetic changes, and the dynamic nature of pregnancy. Although nonpharmacologic interventions are likely safest, they are often ineffective, and a patient is left dealing with frustrations of the sleep disturbance, as well as the negative outcomes of poor sleep in pregnancy. As with any other condition in preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
15

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 101 publications
1
51
0
15
Order By: Relevance
“…98 This report suggested that based on the available literature, perceived risks of narcolepsy medications might be overestimated, 98 however current studies indicate the potential of teratogenicity of certain therapies and treatment of narcolepsy during pregnancy should consider all potential risks and benefits and should include informed collaboration between patient, sleep doctor and obstetrician. 99,100 Challenges for women with narcolepsy who choose to go without medication during pregnancy and lactation are likely to include compromised safety to both mother and fetus/infant as well as increased work absences and potential for unemployment for working women due to poor symptom control. 101 Simply anticipating these challenges could make embarking on family life a difficult consideration for young adult women with narcolepsy and may, in part, explain the increased age at first pregnancy for NT1 women and increased likelihood for single-pregnancy discovered in recent retrospective cohort and case-control studies.…”
Section: Individuals Of Childbearing Potentialmentioning
confidence: 99%
“…98 This report suggested that based on the available literature, perceived risks of narcolepsy medications might be overestimated, 98 however current studies indicate the potential of teratogenicity of certain therapies and treatment of narcolepsy during pregnancy should consider all potential risks and benefits and should include informed collaboration between patient, sleep doctor and obstetrician. 99,100 Challenges for women with narcolepsy who choose to go without medication during pregnancy and lactation are likely to include compromised safety to both mother and fetus/infant as well as increased work absences and potential for unemployment for working women due to poor symptom control. 101 Simply anticipating these challenges could make embarking on family life a difficult consideration for young adult women with narcolepsy and may, in part, explain the increased age at first pregnancy for NT1 women and increased likelihood for single-pregnancy discovered in recent retrospective cohort and case-control studies.…”
Section: Individuals Of Childbearing Potentialmentioning
confidence: 99%
“…Limited research supports meditation, yoga, exercise, and improved sleep quality as potential strategies for prevention and treatment of maternal stress, anxiety, and depression (91)(92)(93)(94)(95)(96)(97). Available studies suggest that regular moderate exercise during lactation improves cardiovascular fitness, plasma lipids, and insulin response.…”
Section: Non-dietary Interventions To Improve Breastfeeding Successmentioning
confidence: 99%
“…13 There are also various pharmacotherapy options for insomnia and other sleep disorders, but human data regarding pregnancy and breastfeeding are largely lacking and, despite reassuring safety data for certain medications, potential concerns still include congenital anomalies and neonatal withdrawal. 14 Melatonin is a hormone released by the pineal gland primarily to regulate the sleep-wake cycle. Exogenous melatonin supplementation is often used for short-term treatment of insomnia and sleep-wake cycle disturbances and is available over the counter in Canada and the United States, making it widely accessible.…”
Section: Introductionmentioning
confidence: 99%